Evaluation of the Utilization of Infographic Media in Learning at Cisaat Elementary School Subang West Java - Ananka, Ramadhia; Prawiladilaga, Dewi Salma; Ariani, Diana; Nirwana, Januar Ilham (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This mentoring activity aims to enhance the knowledge and skills of elementary school teachers in Cisaat Village in designing, developing, and utilizing infographics for teaching, fostering an engaging and interactive learning environment. Through community service, educators are empowered to evaluate learning resources, following a structured approach. Method: The activity involves sequential steps including preparation, assessment, planning alternative programs, action plan formulation, program implementation, evaluation, and termination. Practical Applications: The implementation of this community service initiative facilitates the enhancement of digital literacy among teachers, particularly in developing infographics for blended learning. Teachers are equipped to create and evaluate infographics while maintaining focus on content, creator, and visual elements.Conclusion: The study underscores the importance of equipping teachers with skills to integrate infographics into teaching, enhancing engagement and interactivity in the learning process. It emphasizes the practical implications of empowering educators through structured evaluation processes in community service initiatives.